Binder removal from pavement samples : evaluation of the ignition oven and a modified bitumen recovery procedure - 273025 Oliver, John; Colgrave, Stephen; Tredrea, Peter; ARRB Transport Research; VicRoads; Australian Asphalt Pavement Association (Victoria, Australia : ARRB Transport Research, 1996)
08